2022
DOI: 10.1177/23259671211073713
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Advanced Academic Degrees in Orthopaedic Sports Medicine Faculty

Abstract: Background: Limited knowledge exists on the role of advanced academic degrees within faculty positions in orthopaedic sports medicine. Purpose: To 1) provide an assessment of the baseline demographics of advanced degrees among orthopaedic sports medicine faculty and 2) examine the impact of advanced degrees on research productivity and career attainment of orthopaedic sports medicine faculty. Study Design: Cross-sectional study; Level of evidence, 4. Methods: Orthopaedic sports medicine academics were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
4
6
0
Order By: Relevance
“…Master's degrees have been shown to be one of the most common additional degrees among orthopaedic faculty, 22,23 which is in line with the results of the present study. In a previous study, 7.1% of faculty across the US held an additional academic degree, while 12.5% of matched residents in 2018 had an additional degree.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Master's degrees have been shown to be one of the most common additional degrees among orthopaedic faculty, 22,23 which is in line with the results of the present study. In a previous study, 7.1% of faculty across the US held an additional academic degree, while 12.5% of matched residents in 2018 had an additional degree.…”
Section: Discussionsupporting
confidence: 91%
“…23 Programs with faculty with advanced degrees were also correlated with a higher program ranking. 23 The overall scarcity of additional degrees in orthopaedics and the apparent benefits to the field that they can provide, present an opportunity for improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, psychological factors were identified as the primary reason for failure to RTSA in 55.9% of the athletes analysed in this review. These findings are consistent with previous elbow and knee research, which identified psychological factors as one of the main obstacles for athletes to RTS after medial ulnar collateral ligament or anterior cruciate ligament reconstruction [7, 27]. In those studies, an important proportion of patients (40.4 and 64.7%, respectively) attributed their failure to RTS to psychological factors [7, 27].…”
Section: Discussionsupporting
confidence: 91%
“…Psychological factors have a well‐recognised impact on determining an athlete's ability to RTS, particularly after knee or elbow reconstructive surgery [2, 7, 27, 45, 47]. Kinesiophobia is an excessive fear of movement that can lead to avoidance of physical activity [9].…”
Section: Introductionmentioning
confidence: 99%